VALUATION OF CONDITIONS OF MECHANIZED MILKING OF COWS AND OF THE MAMMARY HEALTH SITUATION IN THE EAST CENTRAL DE SOUSSE (TUNISIA) - Y. M’Sadak; M. Makhlouf; H. Sboui (Journal of Fundamental and Applied Sciences, 2015)
The aim of this study is to evaluate mainly the conditions the milking and the mammary health status of cows in the central East Sousse (Tunisian Sahel). The study was conducted on a sample of 20 small and means dairy cattle herds aboveground divided into two study areas. This study examined the general conditions of cattle, the practices of trafficking and the situation mammary health of cows, while completing the analysis by assessing quantitative losses caused in the product milk. The situation detected in the elevages requires an effective response against mastitis while trying to control the risk factors in small and medium farms herds aboveground.